2020
DOI: 10.3892/etm.2020.8929
|View full text |Cite
|
Sign up to set email alerts
|

microRNA‑646 inhibits angiogenesis of endothelial progenitor cells in pre‑eclamptic pregnancy by targeting the VEGF‑A/HIF‑1α axis

Abstract: Pre-eclampsia is a complication that occurs during pregnancy, the pathological feature of which is a change in vascular endothelial homeostasis. microRNA (miR)-646 is an anti-angiogenic miRNA that has been indicated to exhibit potential anti-angiogenic effects in endothelial cells cultured in vitro and in ischemia-induced angiogenesis. However, whether miR-646 has therapeutic potential in placental angiogenesis in pre-eclampsia remains to be determined. In the current study, human peripheral blood-derived endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…We observed reduced VEGF-A and VEGFR-2 expression in IUGR-ECFCs. Decreased VEGF-A expression has been observed in preeclamptic pregnancy, an obstetric complication often associated with an increased incidence of IUGR [ 71 ], and in the pancreatic islets of IUGR fetal sheep [ 72 ]. In addition, VEGF was markedly downregulated in EPCs isolated from patients with either coronary heart disease [ 73 ] or from diabetic patients, and is associated with decreased eNOS expression [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…We observed reduced VEGF-A and VEGFR-2 expression in IUGR-ECFCs. Decreased VEGF-A expression has been observed in preeclamptic pregnancy, an obstetric complication often associated with an increased incidence of IUGR [ 71 ], and in the pancreatic islets of IUGR fetal sheep [ 72 ]. In addition, VEGF was markedly downregulated in EPCs isolated from patients with either coronary heart disease [ 73 ] or from diabetic patients, and is associated with decreased eNOS expression [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“… [ 108 ] miR-133 serum upregulated Rho/ROCK MiR-133 may affect the apoptosis of trophoblasts in the placenta tissues [ 109 ] miR-384 placenta/plasma upregulated PTBP3 Cell proliferation and migration were inhibited by miR-384 overexpression [ 110 ] miR-21 Serum/placenta upregulated FOXM1 MiR-21 may regulate placental cell proliferation [ 111 ] miR-125a-5p placenta/exosome upregulated VEGFA miR-125a-5p might affect HTR8/SVneo cell proliferation and migration and inhibit angiogenesis [ 112 ] miR-214-3p serum upregulated PIGF Downregulation of miR-214-3p promoted trophoblast invasion into the decidua, as well as spiral artery remodeling [ 113 ] miR-518b plasma upregulated EGR1 Increased miR-518b inhibited trophoblast migration and angiogenesis [ 114 ] miRNA-646 serum upregulated VEGF-A miR-646 suppressed endothelial progenitor cells (EPCs) multiplication, differentiation and migration. [ 115 ] miR-215-5p placenta upregulated CDC6 miR-215-5p inhibited both the migration and invasive potential of trophoblasts, besides decreasing the G1-S transition in HTR-8/SVneo cells [ 116 ] miR-483 venous blood/ umbilical cord blood / placental tissue downregulate IGF1 miR-483 regulates the expression of PI3K, Akt, and mTOR in endothelial progenitor cells [ 117 ] …”
Section: Mirnas and Preeclampsiamentioning
confidence: 99%
“…In situ hybridization demonstrated that the level of miR-20a was higher in PE than in normal placental tissue, and showed that the up-regulation of miR-20a can inhibit the proliferation, migration, and invasion of trophoblast cells by inhibiting the expression of forkhead box A1 (FOXA1) . In addition, miR-646 expression is elevated in endothelial progenitor cells isolated from the peripheral blood of pregnant women with PE (Dong D. et al, 2020). miR-646 reduces angiogenesis and inhibits the proliferation, differentiation, and migration of endothelial progenitor cells by down-regulating VEGF-A and HIF-1α expression.…”
Section: Roles In Trophoblast Cell Invasionmentioning
confidence: 99%
“…Enhanced IL-6 expression can reduce miR-223 levels, leading to vascular dysfunction and promoting macrophage infiltration, with adverse effects on the invasion of cytotrophoblast cells into the decidua and myometrium (Lockwood et al, 2008). Immunohistochemistry has further demonstrated that the decidua and trophoblast cells of patients with PE exhibit high expression of IL-6 (Lockwood et al, 2008), which is the main factor inducing decreased miR-223 expression Dong D. et al (2020). Low expression of miR-223 in PE may be a compensatory mechanism that activates endothelial function and increases angiogenesis.…”
Section: Roles In Immune Regulation and Inflammationmentioning
confidence: 99%